Multicultural Islamic Preaching within a Plural Society: Ustaz Mursyidin’s Contribution in Penyengat Village, Siak - Hasibuan, Perdamaian; Marpuah, Siti; Masbukin, Masbukin; Hanafi, Imam (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2025)
This article examines the multicultural da'wah practices carried out by ustaz Mursyidin in Penyengat Village, Sungai Apit Subdistrict, Siak Regency, Riau—a traditional community of the Anak Rawa Tribe where most residents adhere to Christianity, Buddhism, and indigenous beliefs, while Muslims form a small minority. The study aims to explore the da'wah strategies used, identify the challenges faced, and analyze community responses within a multicultural setting. Using a qualitative character study approach, data were collected through interviews, participatory observation, and document analysis. Findings reveal that ustaz Mursyidin adopts a contextual and empathetic approach by engaging in da'wah bil hal, interfaith dialogue, and cultural negotiation. These strategies emphasize tolerance, participation, and exemplary conduct. The challenges include conflicts between Islamic values and local customs, as well as symbolic resistance. Nonetheless, the soft and inclusive methods employed led to a high level of acceptance among the community. This study affirms the relevance of multicultural da'wah theories, cultural da'wah, cross-cultural communication, and power relations as foundations for effective da'wah in pluralistic societies. Artikel ini mengkaji praktik dakwah multikultural yang dijalankan oleh Ustaz Mursyidin di Kampung Penyengat, Kecamatan Sungai Apit, Kabupaten Siak, Riau—sebuah komunitas adat Suku Anak Rawa di mana mayoritas penduduknya menganut agama Kristen, Buddha, dan kepercayaan lokal, sementara umat Islam merupakan kelompok minoritas. Penelitian ini bertujuan untuk menguraikan strategi dakwah yang digunakan, mengidentifikasi tantangan yang dihadapi, serta menganalisis respons masyarakat dalam konteks multikultural. Penelitian menggunakan pendekatan kualitatif dengan metode studi tokoh dan observasi partisipatif, disertai analisis dokumen. Hasil penelitian menunjukkan bahwa ustaz Mursyidin menerapkan pendekatan yang kontekstual dan empatik melalui dakwah bil hal, dialog lintas agama, dan negosiasi budaya. Strategi ini menekankan toleransi, partisipasi, dan keteladanan sosial. Tantangan yang dihadapi antara lain benturan nilai antara ajaran Islam dan adat lokal serta resistensi simbolik. Meskipun demikian, pendekatan yang lembut dan inklusif menghasilkan tingkat penerimaan yang tinggi dari masyarakat. Penelitian ini menegaskan relevansi teori dakwah multikultural, dakwah kultural, komunikasi lintas budaya, dan relasi kekuasaan sebagai fondasi dakwah yang efektif dalam masyarakat majemuk.